1954
DOI: 10.1017/s0022172400027315
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of radioactive phosphorus in the influenza virus and its distribution in serologically active virus fractions

Abstract: 1. When the D.S.P. strain of influenza virus A is grown in eggs into which 100 μc. of radioactive inorganic phosphate has been introduced the virus incorporates32P into its structure.2. Some 20–25% of the virus32P is found in the virus phospholipid; the remainder is combined with the virus protein and is probably present in the virus nucleic acid.3. When the virus is disintegrated by ether treatment with the liberation of separate red-cell agglutinating and complement-fixing ‘soluble antigen’ particles the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1955
1955
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The complement-fixing unit was apparently identical with the soluble antigen found in infected tissues, and, by the use of virus labelled with radiophosphorus, Hoyle, Jolles & Mitchell (1954) showed that it carried the whole of the virus nucleic acid. The haemagglutinating particle was apparently a nucleic acid-free enzyme.…”
Section: By W Frisch-niggemeyer and L Hoylementioning
confidence: 78%
See 1 more Smart Citation
“…The complement-fixing unit was apparently identical with the soluble antigen found in infected tissues, and, by the use of virus labelled with radiophosphorus, Hoyle, Jolles & Mitchell (1954) showed that it carried the whole of the virus nucleic acid. The haemagglutinating particle was apparently a nucleic acid-free enzyme.…”
Section: By W Frisch-niggemeyer and L Hoylementioning
confidence: 78%
“…The whole of the nucleic acid of the infective virus particle appears to be carried by the soluble antigen (Hoyle, Jolles & Mitchell, 1954). Since the infective virus contains 0-74 % RNA the soluble antigen accounts for about 14 % of the weight of the infective particle, and a spherical infective particle of diameter 100m,t and a particle weight of 3 x 108 would contain about 70 molecules of soluble antigen.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the dose of 32p Hoyle et al (1954) and Liu et al (1954) produced virus preparations much more heavily labelled than those of Graham. For the purpose of the present work it was necessary to obtain very heavily labelled virus, and it was found that the dose of 32p could be increased to 1 millicurie per egg, and when this was done preparations of virus could be obtained in which the Geiger count per minute per ml.…”
mentioning
confidence: 98%
“…The demonstration by Graham & McLelland (1949, Hoyle, Jolles & Mitchell (1954) and Liu, Blank, Spizizen & Henle (1954) that influenza virus could be labelled with radiophosphorus afforded a possible method of detecting the fate of the infecting particle on entry into the host cell. This paper describes the behaviour of 32p labelled virus introduced as a primary inoculum in fertile eggs and affords direct evidence that the infecting particle becomes disintegrated on entry into the host cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation